Neogene and Quaternary fan-delta deposits in southeastern Spain. Field Guide. - Zazo, Caridad; Dabrio, CRISTINO J.; Santiesteban, C. de; Somoza, L.; Goy, José Luis (Cuadernos de Geología Ibérica, 1991)
Sin resumen